2020
DOI: 10.3390/insects11090578
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of Neotropical Water Striders and Its Potential Role in Codiversification

Abstract: Insects host a highly diverse microbiome, which plays a crucial role in insect life. However, the composition and diversity of microbiomes associated with Neotropical freshwater insects is virtually unknown. In addition, the extent to which diversification of this microbiome is associated with host phylogenetic divergence remains to be determined. Here, we present the first comprehensive analysis of bacterial communities associated with six closely related species of Neotropical water striders in Panama. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…For freshwater insects it has been shown that both the place of sampling and host species determine the microbiome composition (Castillo et al, 2020; Receveur et al, 2020) and similar findings have also been made for freshwater hydras (Fraune & Bosch, 2007). On the other hand, similar feeding mechanisms might filter for similar bacterial taxa, even in distantly related freshwater invertebrates (Lyra et al, 2018).…”
Section: Introductionmentioning
confidence: 61%
“…For freshwater insects it has been shown that both the place of sampling and host species determine the microbiome composition (Castillo et al, 2020; Receveur et al, 2020) and similar findings have also been made for freshwater hydras (Fraune & Bosch, 2007). On the other hand, similar feeding mechanisms might filter for similar bacterial taxa, even in distantly related freshwater invertebrates (Lyra et al, 2018).…”
Section: Introductionmentioning
confidence: 61%
“…Firstly, most aquatic species, especially those of Notonectidae and Belostomatidae, harbored a gut bacterial community of high richness ( Table 1 ) but lacked dominant bacterial taxa, with the top 30 genera detected at relatively low frequencies (average of 0.53, Figure 2 A and Table S3 ). This gut bacterial community profile was also seen in the related water striders (Gerridae, Gerromorpha), which also engage in an aquatic habitat lifestyle [ 47 ]. However, the diversity of the gut microbiota decreased in the species of Nepidae to a level comparable with those terrestrial carnivorous true bugs counterparts ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the carnivorous true bug habitats in aquatic or terrestrial ecological niches, it was noticed that some species of the aquatic habitat possessed a different gut bacterial community, characterized by high bacterial richness. Similarly, water striders (Gerridae, Gerromorpha) engaging in an aquatic habitat lifestyle, such as Nepomorpha bugs, also possessed a high richness of gut bacteria but showed a distinct bacterial taxa composition [ 47 ]. Multiple aquatic true bugs were also found to be characterized by multiple specific bacterial genera compared to the terrestrial true bugs, among which, the genera Phaeovibrio and Desulfovibrio were sulfate- and nitrate-reducing bacteria and pervasive in the water environment, despite a wide distribution across a spectrum of different environments [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second site (Playa Reina lagoon [PR]; 7°37′31.1″N, 81°00′16.7″O) is a typical brackish water (BW) lagoon (~2 ppt), with sandy substrate, and is surrounded by mangrove forest and cativo ( Prioria sp.) trees (Castillo et al., 2020). This site is influenced by both seawater intrusion (due to daily tidal fluctuations) and precipitation (during the rainy season), resulting in salinity levels that can range from 0.4 to 11 ppt (Figure 1b).…”
Section: Methodsmentioning
confidence: 99%